ANALISIS RASIONALITAS DAN EFEKTIVITAS PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH DI SMPN 1 KECAMATAN GUGUAK - Sari, Evita Maila; Lastrioza, Lastrioza; Hadiyanto, Hadiyanto; Irsyad, Irsyad (STKIP Pesisir Selatan, 2025)
A principal's managerial success is determined by their ability to make rational, appropriate, and effective decisions to achieve educational goals. However, this process is not always perfectly rational, as it is influenced by limitations in information, time, and resources. Decision-making is essentially a choice from several alternatives. This study aims to analyze the rationality and effectiveness of decision-making by the principal of SMPN 1 Guguak District based on Herbert A. Simon’s Decision-Making Model. The research employs a descriptive qualitative approach through a literature study, examining theories, research findings, and relevant practices in educational leadership. Data were analyzed using content analysis techniques from various scientific literature sources. The results show that the principal applies the principle of bounded rationality in every decision made. The decision-making process follows the five stages of Simon’s model: intelligence, design, choice, implementation, and evaluation. The effectiveness of the principal’s decisions is reflected in the implementation of policies, acceptance by the school community, and their impact on improving teacher performance and the overall quality of education. Thus, adaptive and data-based rationality is proven to enhance the effectiveness of the principal’s decision-making within the context of modern educational management.